Sanksi Pidana oleh Tindak Pidana Mengedarkan Simpanan Farmasi Kosmetika Tanpa Izin Edar (Studi Kasus Putusan Pengadilan Negeri Denpasar No. Perkara 491/Pid.Sus/2018/PN DPS) - Rafael Aza Pramesuari; I Nyoman Sujana; Diah Gayatri Sudibya (Fakultas Hukum, Universitas Warmadewa, 2021)
This study aims to identify and explain criminal sanctions for cosmetic producers or sellers who do not have this distribution license. The type of research used is normative legal research by analysing cases using the Denpasar District Court Decision Case Number 491/Pid.Sus /2018/ PN DPS. This study uses a statutory approach by examining all laws related to this case, conceptually by combining the opinions of experts so that it becomes the author's legal argument, and the case approach is by using a court decision. The results of the study show that there must be elements that indicate that a person has committed a criminal act, and in this writing there are 3 (three) elements that explain that the defendant committed a criminal act. Imposition by the criminal sanction of distributing cosmetic pharmaceutical deposits that do not obtain a distribution permit as regulated in Law Number 36 of 2009 concerning health is regulated in articles 197-201. In this case, the Panel of Judges considered Article 197, namely a maximum imprisonment of 10 (ten) years and a maximum fine of 1,000,000,000 (one billion rupiah). However, the defendant here does not need to undergo the sentence unless later there is another order from the Judge's decision that he has been guilty of committing a criminal act during the probation period has not ended.